Optimising Indonesia-Malaysia Border Security Operations to Enhance Maritime Security in Support of National Defence - Mustaqim, Faizal; Golkariansyah, Golkariansyah; Hanjar, Hanjar (AGUSPATI Research Institute, 2024)
As an archipelagic country, Indonesia has a long maritime border that raises the potential for disputes with neighbouring countries, especially regarding maritime boundaries. One of the maritime borders still in dispute is the Indonesia-Malaysia maritime border in the Sulawesi Sea, especially in the Ambalat Block area. The Indonesian Government has included the Ambalat Block as part of Indonesian territory. It has exploited the area, as it is a natural continuation of the Kalimantan continental plate and is within 200 nautical miles of the baseline. On the other hand, the Malaysian Government published a Defence White Paper in 2020, which displays a map of the Ambalat Block as part of the State of Malaysia. The boundary dispute in the waters of the Ambalat Block has led to violations of sovereignty and illegal activities, such as drug smuggling, shipping violations, IUU fishing, illegal migrant workers/trafficking and illegal trading. Therefore, this research aims to analyse Indonesia- Malaysia border security operations to improve maritime security and support national defence. The research method used in this study is qualitative. The qualitative method is used to formulate phenomena and information related to the Indonesia-Malaysia border security operations in the Ambalat Block. The phenomena described in this research are the Indonesia-Malaysia maritime boundary in the Ambalat Block that has not been agreed upon by both countries, violations of sovereignty, the potential for illegal activities and the implementation of border security operations that have not been optimal. Efforts need to be made to solve these problems, including the settlement of the Indonesia-Malaysia maritime boundary dispute, increasing the degree of Pamtas Operations, improving facilities and infrastructure to support Pamtas Operations and strategies to optimise the Indonesia-Malaysia Pamtas Operations in the Ambalat Block.